Sumpah Pemuda Arab, 1934: Pergulatan Identitas Orang Arab-Hadrami di Indonesia - Rabith Jihan Amaruli; Nazala Noor Maulany; Singgih Tri Sulistiyono (Jurnal Sejarah Citra Lekha, 2018)
This article discusses the Sumpah Pemuda Arab (Arab Youth Pledge) in 1934 which became the forerunner of the formation of the first Arab-Hadrami nationalist organization, the Arab Association of Indonesia (PAI) which later became the Arab Party of Indonesia (PAI). This article conducted by using the historical method. Sumpah Pemuda Arab 1934 is the answer to the struggle of Arab-Hadrami identity and nationalism to fulfill its right as part of Indonesian citizen (WNI). This historical study is important in view of the fact that the phenomenon of the Arabism movement which is now emerging through the involvement of symbols and the identity of the oneness tends to place Arab-Hadrami as opposed to the direction and commitment of the nation.